Spatial Relationship of Focal Impulses, Rotors and Low Voltage Zones in Patients With Persistent Atrial Fibrillation. (8th February 2016) - SCHADE, ANJA; NENTWICH, KARIN; COSTELLO‐BOERRIGTER, LISA C.; HALBFASS, PHILIPP; MUELLER, PATRICK; ROOS, MARKUS; BARTH, SEBASTIAN; KRUG, JOACHIM; SZOELLOESI, GEZA‐ATILLA; LAPP, HARALD; DENEKE, THOMAS
Relationship of Rotors and Low Voltage Zones: Introduction: Focal impulses (FI) and rotors are sources associated with the initiation and maintenance of atrial fibrillation (AF). Their ablation results in a lower recurrence rate. The aim of this study was to characterize for the first time the spatial relationship between such sources and atrial low voltage zones (LVZ) representing fibrosis. Methods: Twenty‐five consecutive patients undergoing their first ablation for persistent AF were included. Voltage mapping of both atria was done during AF. Endocardial mapping of FI and rotors (sources) was performed using a basket catheter and displayed using RhythmView TM (Topera Inc.) before ablation. Spatial relationship of LVZ and sources was analyzed. Results: LVZs covered 13 ± 12% of right atrial (RA) endocardial surface and 33 ± 25% of left atrial (LA) endocardial surface. The median number of sources was 1 [1–3] in RA and 3 [1–4] in LA. Of LA sources, 18 (30%) were definitely not associated with LVZs or pulmonary vein (PV) antra. Of RA sources, 32 (84%) were remote from LVZ. During ablation of such sources substantial cycle length (CL) prolongation or AF conversion occurred in 11/23 patients (48%). Altogether, 8/11 (73%) of these pertinent sources were located remotely from LVZ and PV antra. Conclusions: There is a wide discrepancy in distribution of LVZ areas and sites of identified rotors. Site and incidence of FIRM sources appear to be unpredictable with atrial substrate mapping. Further prospective, randomized studies are necessary to elucidate the impact of additional ablation of such sources in patients with persistent or longstanding persistent AF.